Republic of Kazakhstan : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation on the Republic of Kazakhstan highlights the economic outlook and fiscal policy. Inflation moderated to single-digit levels and confidence in the banking system strengthened, leading to rapid remonetization and significant dedollarization. The conduct of monetary policy has been complicated by the inflows of private capital, surging oil earnings, and buoyant demand conditions. Although Kazakhstan has made considerable progress in the structural area, the pace of reform implementation has slowed. Rapid growth has translated into lower poverty, but social indicators remain weak.